Clinical characteristics and outcomes of COVID‐19 in people living with HIV in Belgium: A multicenter, retrospective cohort. Issue 5 (9th February 2021) - Nasreddine, Rakan; Florence, Eric; Moutschen, Michel; Yombi, Jean‐Cyr; Goffard, Jean‐Christophe; Derdelinckx, Inge; Lacor, Patrick; Vandekerckhove, Linos; Messiaen, Peter; Vandecasteele, Stefaan; Delforge, Marc; De Wit, Stéphane; et al.
Abstract: The aim of this study was to describe the clinical characteristics and outcomes of coronavirus disease 2019 (COVID‐19) among people living with HIV (PLWH) in Belgium. We performed a retrospective multicenter cohort analysis of PLWH with either laboratory‐confirmed, radiologically diagnosed, or clinically suspected COVID‐19 between February 15, 2020 and May 31, 2020. The primary endpoint was outcome of COVID‐19. Secondary endpoints included rate of hospitalization and length of hospital stay and rate of Intensive Care Unit (ICU) admission and mechanical ventilation. One hundred and one patients were included in this study. Patients were categorized as having either laboratory‐confirmed ( n  = 65), radiologically‐diagnosed ( n  = 3), or clinically suspected COVID‐19 ( n  = 33). The median age was 51.3 years (interquartile range [IQR] 41.3–57.3) and 44% were female. Ninety‐four percent of patients were virologically suppressed and 67% had a CD4 + cell count more than or equal to 500 cells/µl. Overall, 46% of patients required hospitalization and the median length of hospital stay was 6 days (IQR 3–15). Age more than or equal to 50 years, Black Sub‐Saharan African patients, and being on an integrase strand transfer inhibitor‐based regimen were associated with being hospitalized. ICU admission and mechanical ventilation was required for 15% and 10% of all patients respectively. Overall, 9% of patients died while 78 (77%) patients made a full recovery. HIV patients with COVID‐19 experienced a high degree of hospitalization despite having elevated CD4 + cell counts and a high rate of virologic suppression. Matched case‐control studies are warranted to measure the impact that HIV may have on patients with COVID‐19.